EDUKASI TENTANG KHASIAT TANAMAN KECOMBRANG PADA MASYARAKAT RT 09 KELURAHAN LAMBARA SULAWESI TENGAH - Palipadang, Matra Novalia; Tudaan, Leligrafela; Fince, Maria (Jurnal Abdi Insani, 2025)
Kecombrang (Etlingera elatior) is a wild plant that is easily found and is widespread in almost all regions in Indonesia. This plant contains flavonoids, chlorogenic acid and quercetin which have been proven to have the ability to lower blood glucose levels. Kecombrang in addition to being a food ingredient can also be efficacious as a medicine because it has several pharmacological effects. Kecombrang have a high selling value (economic) and for health can be processed into various forms of preparations ranging from infusions, tea, cream, ointment, soap or even capsules. To realize this, it is necessary to provide educational counseling about the efficacy of the kecombrang plant. Community service aims to provide information about the benefits of kecombrang plants and increase knowledge and the selling value of these plants in the community. The method of implementing community service is a lecture using visual media in the form of a banner about the benefits of kecombrang for health. The target of the community service implementation is the community of RT 09, Lambara Village, Central Sulawesi Province, was carried out in November 2024. The instrument used a questionnaire, with a total sampling technique. Analysis of the results of community service is a univariate analysis in the form of a description of the knowledge of the benefits of kecombrang for health. The results of community service obtained the level of community knowledge before being given counseling, the majority were sufficient, and after being given counseling, knowledge increased where the majority had good knowledge.